PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT DAN DIGITAL MARKETING TERHADAP LOYALITAS KONSUMEN PADA FAZIA BEAUTY KOTA METRO - Sastya Putri; Harits Kurniawan; Denny Kurniawan (Strategic: Journal of Management Sciences, 2024)
The desire to look attractive has a significant impact worldwide, including in Indonesia. Where the cosmetics industry is one of the rapidly growing sectors. In recent years, local brands in the Indonesian cosmetics industry have rapidly increased, especially from large companies and small to medium-sized enterprises. Quantitative research is based on the philosophy of positivism to study a specific population or sample. Research instruments are used to collect data, and hypotheses are tested through quantitative and statistical analysis of that data. This research uses the SPSS 26 statistical program to explain the influence of customer relationship management and digital marketing on consumer loyalty at Fazia Beauty Metro City. The Sig value of the Customer Relationship Management variable is 0,00 < 0,05, which can be concluded that there is an influence of Customer Relationship Management on Consumer Loyalty. The Sig value of the Digital Marketing variable is 0,00 < 0,05, which can be concluded that is an influence of digital marketing on consumer loyalty.